Exact Solutions for Unsteady Free Convection Flow Over an Oscillating Plate Due to Non Coaxial Rotation - Zulkhibri, Ismail; Ahmad Qushairi, Mohamad; Khan, Ilyas; Sharidan, Shafie (SpringerOpen, 2016)
Non-coaxial rotation has wide applications in engineering devices, e.g. in food processing such as mixer machines and stirrers with a two-axis kneader, in cooling turbine blades, jet engines, pumps and vacuum cleaners, in designing thermal syphon tubes, and in geophysical flows. Therefore, this study aims to investigate unsteady free convection flow of viscous fluid due to non-coaxial rotation and fluid at infinity over an oscillating vertical plate with constant wall temperature.